BADRدور التدقيق الداخلي في إدارة مخاطر السيولة دراسة حالة ببنك الفالحة والتنمية الريفية - سحنون طه ياسين; مداح محمد; حساب محمد لمين (جامعة عمار ثليجي -الأغواط كلية العلوم الاقتصادية و التجارية و علوم التسيير, 2022)
This study aimed to know the role and importance of internal audit in managing liquidity risks. Risk management is one of the most important functions in banks, which works to cover and address all possible risks, but its success requires the assistance of a group of parties at the bank level, especially the internal auditor, as Internal audit plays an important role in activating risk management. Through a case study in the Bank of Agriculture and Rural Development, Laghouat branch, we found that to achieve effectiveness in auditing liquidity risk management, coordination and integration must be achieved between both the risk management department and the internal audit function while ensuring the independence of each one. Key words: Internal audit, risk management, Basel committee, banking risk management, liquidity risk